The shortest history of war - Dyer, Gwynne, 1946- (Exeter)
241, [2] sayfa
Keywords: “In this addition to the bestselling ‘shortest history’ series, acclaimed historian and military expert Gwynne Dyer tells the story of war from its prehistoric – perhaps pre-human – origins up to the present age of algorithms and atom bombs. Dyer chronicles the spread of warfare in the world’s first cities; the seemingly inexorable rise of inequality and tyranny as human societies expand; the millennium-long ‘classical age’ of combat ended by the firearm and the carnage of the Thirty Years’ War; the brief ensuing interlude of ‘limited war’ before the popular revolutions of the 18th century ushered in an era of total war – itself abruptly halted by Hiroshima. The final chapters deal with the precarious equilibrium of the past 75 years – the longest period of peace between major powers in modern history – and with the looming threats of nuclear proliferation, superpower rivalry and climate change“ --